Analisis Penawaran dan Permintaan Komoditas Kedelai (Glycine Max L.) di Provinsi Jawa Timur - Mohammad Akbar Rizki Ramadhan; Hary Sastryawanto; Endang Siswati (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2022)
The purpose of this study is to find out the factors that influence the supply and demand of soybeans and predict the supply and demand of soybeans in East Java in the next 10 years. The data used is Secondary data that has been collected by research institutions and published to data users. The results of the analysis on supply show that there are three factors that have a significant influence on soybean supply in East Java, namely land area, domestic soybean prices, and productivity. Meanwhile, other factors, namely the price of corn and the price of imported soybeans, do not affect the soybean supply in East Java. Of the four factors contained in the soybean demand model in East Java, there is one factor that has a significant influence on the demand for East Java soybeans, namely the population. Meanwhile, other factors are domestic soybean prices, imported soybean prices and income levels. The prediction of East Java soybean supply for the next 10 years will decrease every year until 2030 and the prediction of East Java soybean demand for the next 10 years will increase every year.Keywords: Trend Analysis, Supply and Demand, Soybean, Corn, Land Area